Lipid Polarity Is Maintained in Absence of Tight Junctions - Ikenouchi, Junichi; Suzuki, Mayu; Umeda, Kazuaki; Ikeda, Kazutaka; Taguchi, Ryo; Kobayashi, Tetsuyuki; Sato, Satoshi B.; Kobayashi, Toshihide; Stolz, Donna B.; Umeda, Masato (The Journal of biological chemistry, 2012)
The role of tight junctions (TJs) in the establishment and maintenance of lipid polarity in epithelial cells has long been a subject of controversy. We have addressed this issue using lysenin, a toxin derived from earthworms, and an influenza virus labeled with a fluorescent lipid, octadecylrhodamine B (R18). When epithelial cells are stained with lysenin, lysenin selectively binds to their apical membranes. Using an artificial liposome, we demonstrated that lysenin recognizes the membrane domains where sphingomyelins are clustered. Interestingly, lysenin selectively stained the apical membranes of epithelial cells depleted of zonula occludens proteins (ZO-deficient cells), which completely lack TJs. Furthermore, the fluorescent lipid inserted into the apical membrane by fusion with the influenza virus did not diffuse to the lateral membrane in ZO-deficient epithelial cells. This study revealed that sphingomyelin-cluster formation occurs only in the apical membrane and that lipid polarity is maintained even in the absence of TJs. Tight junctions (TJs) are thought to prevent lipids from diffusing freely between the apical and basolateral membrane. We demonstrated that lipids from the apical and basolateral membranes are segregated in an epithelial cell line lacking ZO-proteins. TJs are not essential for the maintenance of lipid polarity in epithelial cells. We demonstrated that the formation of TJs and lipid polarity occurs independently in epithelial cells.